The concept of resistance in colonial Africa: recomposing a paradigm - Paiva, Felipe (2019)
Analysis of the historiographic trends that sought to define a historiographic concept for the African anticolonial resistance. It seeks to understand the emergence of studies on African resistance, inserting them in their due historical context. Subsequently, we present critically some contemporary caveats made to this model.The last part of the work is composed of a theoretical proposal proper to the African anti-colonial resistance.